EDUCATIONAL MANAGEMENT IN THE AGE OF SOCIAL MEDIA – A LITERATURE REVIEW - Nasrudin, Dindin -; Kasmin, Kasmin (Universitas Muhammadiyah Surakarta, 2019)
In recent years there has been an increasing interest in educational management. Specially in this social media era. This article presents an exhaustive review of educational management studies and suggests a direction for future developments. This research was conducted by comparing several articles (literature study) from educational management journals. This literature study was conducted by analyzing forms of educational management in the era of Social media. From the results of the literature study, it can be seen how the documentation technique in management education in the era of Social Media. The results presented here may facilitate improvements in the educational field. The presence of technology makes management in the field of education was easy to run. In the data documentation section, there are many applications that can be used to streamline school administration time and personnel. In addition, information dissemination is easier and class management makes students more active in asking questions and getting fast feed back from the teacher